Analysis of fatigue failure mode transition in load-carrying fillet-welded connections. (March 2016) - Xing, Shizhu; Dong, Pingsha; Threstha, Alina
Abstract: In load-carrying fillet welded connections, two distinct fatigue failure modes are possible depending upon fillet weld leg size and loading conditions. One is weld toe cracking through base plate thickness and the other is through weld metal, often referred to as weld root cracking. Based on a recent comprehensive fatigue testing program in support of construction of lightweight ship structures, this paper examines a number of stress based fatigue parameters that can be used to formulate an effective criterion for determining failure mode transition from weld root to weld toe. A closed form solution has been developed for analytically determining the weld throat critical plane on which a traction stress based fatigue parameter attains its maximum and can be compared with that corresponding to weld toe cracking. It is found that both an effective weld throat stress based criterion by combining normal and shear traction stresses and an equivalent effective stress based criterion based on the master S-N curve formulation can be used for the determination of the minimum fillet weld leg size beyond which weld toe fatigue failure dominates. The proposed fillet weld sizing criteria are then validated using a large amount of fatigue test data on load-carrying cruciform fillet welded specimens. Highlights: Presented an analytical model for weld throat cracking in fillet welds. Established fatigue failure mode transition criterion from weld root to toe cracking. Validated by over 200 fatigue tests performed by this study.